The rights in the care relationship in elderly home: https://doi.org/10.53809/2021-01-TS-n.1-132-147 ("Temas Sociais" Journal, 2021)
Social workers in the development of the care relationship with elderly people integrated in elderly home, aim at well-being, dignity and rights. This care relationship transports to ethical values ​​and principles, in the effective guarantee of the dignity and rights of the elderly. This article deals with the care relationship developed by social workers with elderly people integrated in elderly home, in a qualitative approach, through documentary research, in order to broaden the debate on the development of the care relationship, starting from ethics, dignity and the rights of elderly people integrated into the home. Every care relationship must develop based on values, self-determination, decision-making power, individualization, dignity and respect. Through this action, training is developed, free decision-making, the guarantee of respect for convictions, needs and privacy. The rights, desires and tastes of the elderly are still invisible in the care relationship, so there is a need to be an effective practice.
Keywords: dignity; rights; relationship; care; elderly